2020
DOI: 10.1002/jbm4.10439
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of Enpp6 Results in Transient Bone Hypomineralization

Abstract: Biomineralization is a fundamental process key to the development of the skeleton. The phosphatase orphan phosphatase 1 (PHOSPHO1), which likely functions within extracellular matrix vesicles, has emerged as a critical regulator of biomineralization. The biochemical pathways which generate intravesicular PHOSPHO1 substrates are however currently unknown. We hypothesized that the enzyme ectonucleotide pyrophosphatase/phosphodiesterase (ENPP6) is an upstream source of PHOSPHO1 substrate. To test this, we charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
(115 reference statements)
0
3
0
Order By: Relevance
“…( 68 ) This observation aligns with the hypothesis that the specific distribution of these PCs and LPCs in the growth plate is linked to biomineralization as proposed. ( 51 , 52 ) Therefore, we aimed to determine if PCs and LPCs enriched in the growth plate are involved in the PHOSPHO1‐mediated accumulation of P i .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…( 68 ) This observation aligns with the hypothesis that the specific distribution of these PCs and LPCs in the growth plate is linked to biomineralization as proposed. ( 51 , 52 ) Therefore, we aimed to determine if PCs and LPCs enriched in the growth plate are involved in the PHOSPHO1‐mediated accumulation of P i .…”
Section: Resultsmentioning
confidence: 99%
“…It has been proposed that MV membrane remodeling under the action of an unidentified phospholipase A2 (PLA2) enzyme converts phosphatidylcholine (PC) lipids to a lyso‐phosphatidylcholine (LPC) lipid intermediate, which is subsequently hydrolyzed by ectonucleotide pyrophosphatase/phosphodiesterase 6 (ENPP6) to generate the PCho substrate for PHOSPHO1. ( 51 ) The involvement of ENPP6 as an upstream mediator of PHOSPHO1 function was recently supported by the hypomineralized phenotype observed in ENPP6‐null mice. ( 52 ) Nevertheless, the precise role of PHOSPHO1 in lipid homeostasis and metabolism during bone mineralization in the growth plate is yet to be elucidated.…”
Section: Introductionmentioning
confidence: 96%
“…Consistently, Phospho1 −/− mice displayed hypo-mineralization of the bone at birth, biomechanical incompetency, scoliosis, and spontaneous greenstick fractures [ 61 , 62 ]. More recently, Dillon et al demonstrated ectonucleotide phosphodiesterase/pyrophosphatase member 6 ( Enpp6 ) −/− mice also revealed hypo-mineralization [ 63 ]. ENPP6 is a member of the nucleotide pyrophosphatase/phosphodiesterase family with lysophospholipase C activity, generating phosphocholine with a monoacylglycerol byproduct [ 64 , 65 , 66 ].…”
Section: Matrix Vesicle-meditated Mineralizationmentioning
confidence: 99%